Indonesian Interests in Hadith-Sourced COVID-19 Queries According to Google Trends - Ali Imron (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2021)
COVID-19 pandemic has had an impact on people’s religious lives all around  the world. This article attempts to examine the following hypothesis: COVID-19 also influences religious life in Indonesia, the results of which can be also observed in hadith studies. This study employed a mixed-method. The data is compiled through Google Trends (GT) from 1 December 2019 to 20 August 2020, pointing to four keywords. The data is analyzed through a content analysis. This research suggests that there is an exponentially increasing search using those four words on the internet. The search for hadiths on COVID-19 was only conducted in West Java. ‘Doa Covid’ (prayer for protection from COVID-19) became the most exponentially searched keyword across Indonesia. The GT data suggests that individuals are searching the internet for an explanation about the prophetic guideline in dealing with COVID-19. The most popular articles are published in Republika Online, Tribun Newsgroup, MadaniNews, Okezone, and Liputan6. The hadiths mentioned in those articles contain mostly the prayers of the Prophet Muhammad to keep people away from illness or to obtain safety in the world and the afterlife.